The crucial role of intercultural competence in promoting global citizenship among Moroccan higher education students (Journal of Applied Learning and Teaching, 2026)
In an era marked by increasing globalization and cultural tensions, fostering intercultural competence (IC) is essential for promoting a new form of global citizenship, particularly among Moroccan students. This paper explores the pivotal role of Higher Education (HE) institutions in Morocco in cultivating this competence to prepare students for a diverse, interconnected world. IC encompassing knowledge, skills, and attitudes are fundamental in preventing cultural misunderstandings and promoting unity. Morocco's unique position as a cultural crossroads, with its blend of African, European, and Middle Eastern influences, makes it an ideal setting for the development of this competence. While Moroccan HE strategies are rich in diversity, and Moroccan instructors assert the importance of the potential for intercultural learning remains underutilized. This opinion article argues that by positioning IC at the heart of internationalization efforts, intentionally integrating IC into the core curriculum, promoting cultural exchange, and providing faculty development, Moroccan universities can better equip students to navigate global challenges. Drawing on Deardorff’s (2006) Pyramid Model of Intercultural Competence, this paper evaluates current local practices, such as Erasmus+ programs, and proposes additional measures, including mandatory intercultural courses, language programs, extracurricular initiatives, and international exchange opportunities, to foster these skills. Ultimately, by nurturing IC, Moroccan students can become responsible global citizens, contributing to social cohesion, regional stability, and international peace. Beyond the Moroccan context, this discussion contributes to the larger understanding of how HE systems, can align internationalization efforts with intercultural goals. The insights drawn from Morocco’s reforms may also serve as a reference for other countries navigating similar tensions between global competitiveness and humanistic goals of education.